EDUKASI CARA MENDAPATKAN DAN MENYIMPAN OBAT DI CLUSTER JADE BEKASI - Niko Prasetya; Vonny Nofrika; Fitri Savitri; Dessy Adelia (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2021)
Dagusibu is a drug handling step as an abbreviation of Get, Use, Save, and Dispose of. So as consumers, we must know how to get, use, store, and dispose of the medicines we have. Not all people know and understand how to handle this drug, so information about this is important to be disseminated to the public. A study in the RW 06 area of ​​Cakung Timur Sub-district showed that as many as 53.2% of respondents had less knowledge about Dagusibu antibiotic drugs (Miranti, 2019). The outreach activity aims to increase public knowledge about how to get and store good medicines in the residents of the Jade Cluster, East Bekasi, Bekasi City. Based on the results of community service activities in the residents of the Jade Cluster, East Bekasi, Bekasi City, it can be concluded that the counseling carried out was able to increase knowledge about how to obtain and store good medicines.